(untitled) (Educação em Revista, 2022)
Moving from initial teacher education into teaching can be difficult. In Scotland, a guaranteed induction year for those who meet the Standard for Provisional Registration helps the transfer from student to teacher with the provision of an induction supporter/mentor and a reduced teaching load. However, after the induction year the mentoring and reduction in teaching stops and there is no specific assistance organised for early career teachers at a national or local authority level. This paper reports on the issues that early career teachers face in the transition from induction year teacher to fully registered teacher in Scotland. During a two-year mixed-methods study of induction year teachers in Scotland, four participants were interviewed after their first year of teaching which is their first year as a fully registered teacher. In semi-structured interviews the teachers were asked about their professional learning and support needs. The participants highlighted issues related to changing schools, working as a supply teacher, learning from observations, support from colleagues, relationships with pupils and their future career. The research shows how there is an ongoing need for support for early career teachers beyond their induction year in Scotland.